Respostas
respondido por:
2
(a + b)² = a² + 2ab + b²
(√201+√199) * (√201+√199) = (√201+√199)²
(√201+√199)² = (√201² + 2*√201*√199 + √199²) =
( 201 + 199 + 2*√201*√199) = 400 + 2*√[(200+1)(200-1)] =
400 + 2*√(200² - 1) = 400 + 399.995 ~ 800
(√201+√199) * (√201+√199) = (√201+√199)²
(√201+√199)² = (√201² + 2*√201*√199 + √199²) =
( 201 + 199 + 2*√201*√199) = 400 + 2*√[(200+1)(200-1)] =
400 + 2*√(200² - 1) = 400 + 399.995 ~ 800
respondido por:
0
Resposta:
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás